КУЛЬТУРНО-ФИЛОСОФСКАЯ ЭКСПЛИКАЦИЯ СВЕРХЧЕЛОВЕЧЕСКОГО ОБРАЗА В КОНТЕКСТЕ ГУМАНИЗМА И ОБЩЕСТВЕННОМ ДИСКУРСЕ - Печёркина, М.В.; Крамок, З.С.; Бексултанов, Д.Т.; Альшанова, Б.Х. (My University, 2019)
Аннотация В рассматриваемой статье формулируются ключевые тезисы, объясняющие проблему сверхчеловеческого в ницшеанской картине мира. Актуальность данного исследования состоит в закономерно обусловленной предрекаемости появления сверхчеловека как про- дуцента критики морали декаданса. Целью исследования служит рассмотрение идеи сверхчеловека как комплексной меж- дисциплинарной категории, включающей в себя религиозно-философский, гуманистический и культурно-просветительский аспекты. Abstract In our article we construct a key theses explaining the problem of over human in the Nietzche`s concept about Ubermensh. Actuality of research consist in right and causal predictability of over human`s appearance as an produce of critics of decadence moral. Goal of our research is a consideration of over human`s idea like an complex interdisciplinary characteristics including religious philosophy humanistic and cultural aspects.
Сultural and philosophical explication of the overman`s form in the context of humanism and public debate
Keywords: ницшеанство; сверхчеловек; воля; власть; имморализм; антиценности; самоценность; nietzcheanism; overman; will; control; freedom; immoralism; anti-value; self- worth